High repetition-rate photoinjector laser system for S3FEL - Zhang, Baichao; Li, Xiaoshen; Liu, Qi; Zhu, Zexiu; Zhang, Weiqing; He, Zhigang; Liu, Wei; Wu, Guorong; Yang, Xueming (Frontiers in Physics, 2023)
The photoinjector laser system of Shenzhen Superconducting Soft X-Ray Free Electron Laser (S3FEL) is reported in this paper. This laser system operates at up to 1MHz and produces more than 50uJ infrared (IR) laser pulses. With a customized fourth harmonic generation (FHG) module, more than 2uJ ultraviolet (UV) laser pulses were obtained. The power standard deviations of the IR laser and the UV laser are 0.093% and 0.395% respectively. While the pulse energy standard deviations are 1.087% and 1.746% correspondingly. We implemented the pulse stacking scheme to generate flat-top pulses. With four birefringent uniaxial crystals, the gaussian pulses were converted to flat-top shape, featuring 10ps pulse width and 0.5ps rising and falling edge. A cut-Gaussian transverse profile with very sharp rising and falling edge can be produced after the spatial pulse shaper.